All sail set a romance of the Flying Cloud - Sperry, Armstrong 1897- (Boston D.R. Godine, 1984)
When his father loses his fortune, a boy is taken on by a famous shipbuilder and eventually makes a maiden, record-breaking trip around Cape Horn on the "Flying Cloud."
Title on added t.p.: The Flying Cloud, clipper, 1851-1874.
Keywords: McKay, Donald -- 1810-1880. -- Juvenile fiction; McKay, Donald -- 1810-1880. -- Fiction; Flying Cloud (Clipper-ship) -- Juvenile fiction; Flying Cloud (Clipper-ship) -- Fiction; Clipper ships -- Fiction; Sea stories